Approaching the Apocalypse a short history of Christian millenarianism - Court, John M. (Tauris, 2008)
Plague, earthquake and flame: ideas about divinely-inspired disaster and prophecies of doom have an enduring place in the history of Christian thought. For centuries men and women have made preparations for the imminent end of the world, and for the thousand year reign of Christ and his saints. Inspired principally by the startling texts of the Book of Revelation, Christianity has a rich and varied tradition of looking forward to the purifying fires of Armageddon. But what do recurring motifs like the Rapture, pestilence, biblical prophecy and the building of the New Jerusalem really add up to? And how have interpretations of these patterns differed from century to century? Charting a steady course between the feverish predictions of early Christian heretics like the Montanists, and the febrile outpourings of modern-day millennialists such as the Branch Davidians and Christian Zionists in America, John M. Court explores the continuities and differences between their violent visions of cataclysm. His history comprises an incisive analysis of such movements and figures as the Levellers and Diggers, James Jezreel and his Trumpeters, Seventh-Day Adventists and Jehovah's Witnesses, cargo-cults and drug cultures. Embracing two thousand years of intense and fiery admonition, Approaching the Apocalypse offers students of religion, history and politics the definitive handbook to Doomsday.